Vietnam : 2005 Article IV Consultation; Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Vietnam. (IMF Staff Country Reports; Country Report ;, 2006)
This 2005 Article IV Consultation for Vietnam reports that high credit growth in the context of weak bank balance sheets remains a cause for concern. The overall fiscal deficit narrowed from 7.2 percent of GDP in 2003 to 4 1\2 percent of GDP in 2004, but a growing program of off-budget operations has weakened fiscal transparency and heightened concerns about medium-term debt sustainability. Improvements in the reliability, timeliness, and dissemination of key data are urgently needed to enhance the quality of policy analysis and surveillance.